2020
DOI: 10.1158/0008-5472.can-20-0263
|View full text |Cite
|
Sign up to set email alerts
|

A Wnt-Induced Phenotypic Switch in Cancer-Associated Fibroblasts Inhibits EMT in Colorectal Cancer

Abstract: Tumor progression is recognized as a result of an evolving cross-talk between tumor cells and their surrounding nontransformed stroma. Although Wnt signaling has been intensively studied in colorectal cancer, it remains unclear whether activity in the tumor-associated stroma contributes to malignancy. To specifically interfere with stromal signals, we generated Wnt-independent tumor organoids that secrete the Wnt antagonist Sfrp1. Subcutaneous transplantation into immunocompetent as well as immunodeficient mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…Interestingly, by generating Wnt-independent tumor organoids, which secreted the Wnt antagonist Sfrp1, Mosa et al found that Sfrp1 or genetic depletion of β-catenin strongly decreased the number of cancer-associated myofibroblasts (myCAFs: α-SMA + /Acta2 + ). 187 Coculture of this tumor organoid with inflammatory CAFs (iCAFs: IL-6 + /Tnfa + /IL-1a + ) resulted in the upregulation of Vim and Zeb1, while myCAFs reverse this upregulation, 187 indicating that the EMT process could be induced by Sfrp1 and that tumor behaviors were differentially regulated via Wnt signaling pathway in specific CAF subtypes.…”
Section: Major Signaling Pathways and Targeted Therapies In Cafsmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, by generating Wnt-independent tumor organoids, which secreted the Wnt antagonist Sfrp1, Mosa et al found that Sfrp1 or genetic depletion of β-catenin strongly decreased the number of cancer-associated myofibroblasts (myCAFs: α-SMA + /Acta2 + ). 187 Coculture of this tumor organoid with inflammatory CAFs (iCAFs: IL-6 + /Tnfa + /IL-1a + ) resulted in the upregulation of Vim and Zeb1, while myCAFs reverse this upregulation, 187 indicating that the EMT process could be induced by Sfrp1 and that tumor behaviors were differentially regulated via Wnt signaling pathway in specific CAF subtypes.…”
Section: Major Signaling Pathways and Targeted Therapies In Cafsmentioning
confidence: 98%
“… 186 Similarly, in colorectal cancer, Mosa et al generated a Wnt3 HA/HA APC min/+ mouse model and demonstrated a direct role of Wnt signaling in fibroblast activation, contractility, and CAF phenotypic plasticity. 187 Importantly, β-catenin ablation reduced the expression of PDGFRα and FSP1 with no obvious cytoskeletal rearrangement in stromal fibroblasts, 188 noting that other signaling pathways might be implicated in the process of cytoskeletal rearrangement mediated by noncanonical Wnt signaling cascade. It has been shown that β-catenin also forms a β-catenin/E-cadherin complex that contributes to the motility and migration of fibroblasts.…”
Section: Major Signaling Pathways and Targeted Therapies In Cafsmentioning
confidence: 99%
“…To validate this speculation, correlation analyses were performed to explore the relationship between the FSTL3 expression and marker genes of those immune cells. CAFs, also the main cellular component in TME, are known to be involved in regulating inflammatory responses, tumor cell proliferation and migration, as well as TME remodeling by secreting matrix degrading enzymes, cytokines and growth factors (34)(35)(36). Correlation heatmap showed that FSTL3 was significantly positively correlated with CAF-associated genes and had a strong positive correlation with TGFB1 (gene encoding TGF-b) (Figure 10A).…”
Section: Correlation Between Fstl3 and Immune Modulators In Crcmentioning
confidence: 99%
“…Mosa and colleagues reported that Wnt activity in CAFs is linked to distinct CAF subtypes: low or high Wnt levels induce inflammatory-like CAFs (iCAFs) or contractile myofibroblastic CAFs (myCAFs) subtypes, respectively. These authors showed that the co-culture of tumor organoids with iCAFs resulted in a significant upregulation of epithelial-to-mesenchymal markers, while myCAFs reverted this phenotype [ 159 ]. The co-culture of mouse intestinal organoids with macrophages and fibroblasts also revealed that these stromal cells can hyperactivate the PI3K signaling in colonic epithelial cells that already carry Kras and Tp53 mutations and that oncogenic mutations cell-autonomously mimic an epithelial signaling state normally induced by stromal cells [ 160 ].…”
Section: Organoid Limitations and New 3d Modelsmentioning
confidence: 99%